Innovation and Surgical Care in Nursing - Yildiz, Kerem; Kaya, Ufuk; Dal Yilmaz, Umran (Galenos Publ House, 2021)
Innovation makes contributions to the patient care process, work order, and the speedup of development. Innovative products consist of technological tools for preventing illnesses, reducing the time of hospitalization, increasing patient comfort, and making the care professional. Florence Nightingale emphasized the need for using innovative products saying We should change life instead of complying with it and gave place to important transformations in health. While determining the technology they will use in the care of surgical patients, nurses should actualize the care practices paying attention to these practices being applicable, employable, and creditable and their legal and ethical aspects. Innovative technology is used in many areas of surgery, and this fact propounds the importance of innovation in surgical care. Studies in which innovative practices are applied in nursing are insufficient ffi cient in our country. For this reason, it is thought that innovative practices in nursing need to be developed. In this review, it is aimed to draw attention to the necessity and importance of innovation in nursing.
Keywords: Innovation; Nursing care; Surgical innovation; Technology